Imido-pyridine Ti(iv) compounds: synthesis of unusual imido–amido heterobimetallic derivatives1. Issue 24 (28th June 2015) - Pedrosa, Sergio; Vidal, Fernando; Lee, Lucia Myongwon; Vargas-Baca, Ignacio; Gómez-Sal, Pilar; Mosquera, Marta E. G.
<x xml:space="preserve">Abstract</x> Controlled generation of novel bridging or terminal imido-pyridine complexes is achieved, including the unusual species [Li(THF)][Ti(η5-C5Me5)(NR)(NHR)2]. Computational studies corroborate its charge-separated nature.